Rancangan Penyusunan Laporan Keuangan berdasarkan Standar Akuntansi Keuangan Entitas Mikro, Kecil dan Menengah (SAK EMKM) pada UMKM Makaroni Nyinyir - Anisya Hilmia; Ahmad Syarief (Indonesian Accounting Literacy Journal, 2022)
The purpose of this study was to determine the accounting system, to determine the design of the bookkeeping process, the design of the preparation of financial statements based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) at Makaroni Nyinyir SMEs. The benefits of this research are as reference material for further research and as input for MSME actors in making financial reports in accordance with SAK EMKM. The research method used by the author in this study is a descriptive qualitative research method. Data collection techniques used are interviews and documentation. The results of this study indicate that the company has only recorded cash receipts and disbursements in a single entry and has not prepared financial statements in accordance with applicable standards. So to solve these problems, the authors designed the bookkeeping process and drafted the preparation of financial statements. The report prepared by the author is the report on the cost of production, the income statement, the statement of financial position and notes to the financial statements in accordance with SAK EMKM in June 2021. With this research, it is hoped that Makaroni Nyinyir can know and be able to prepare financial statements in accordance with SAK EMKM.